The capacitive component of double layer current in plasma - Hrechko, Ya.O.; Azarenkov, N.A.; Babenko, Ie.V.; Ryabchikov, D.L.; Sereda, I.N.; Shovkun, M.A.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2017)
The features of nonstationary double layers in the high-current pulsed discharges have been theoretically and experimentally investigated in this paper. The expression for the capacity of strong double layer in quasi-MHD approximation has been obtained and the area of its applicability has been indicated. The equation for the capacitive component of the double layer current has been derived in this paper. The dynamics of the double layer current capacitive component in the high-current pulsed discharge and the way to verify the calculations has been shown. Теоретически и экспериментально исследуются особенности нестационарных двойных слоёв в сильноточных импульсных разрядах. В квази-МГД-приближении получено выражение для ёмкости сильного двойного слоя и указана область его применимости. Получено уравнение для ёмкостной составляющей тока двойного слоя. Показана динамика ёмкостной составляющей тока двойного слоя в сильноточном импульсном разряде и приведен способ верификации расчётов. Теоретично та експериментально досліджуються особливості нестаціонарних подвійних шарів у си-льнострумових імпульсних розрядах. У квазі-МГД-наближенні отримано вираз для ємності сильного подвійного шару та вказана область його застосування. Отримано рівняння для ємнісної складової струму подвійного шару. Показана динаміка ємнісної складової струму подвійного шару в сильнострумовому імпульсному розряді та приведено спосіб верифікації розрахунків.